2020
DOI: 10.3390/jcm9051516
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells in Immunity and Disease: A Better Understanding for an Improved Use

Abstract: In this Special Issue, directed and supervised by Dr. Mehdi Najar, a collection of basic research articles and reviews, on the state of the art of Mesenchymal Stem/Stromal Cells (MSCs) immune biology, is presented. Among the major goals of this Special Issue is the presentation of an update about the immunomodulatory properties of MSCs and their capacity to respond to tissue microenvironment changes. MSCs hold great promise in the field of immunotherapy and regenerative medicine. Accordingly, a better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…These observations support the current view that MSCs properties are impacted by the tissue origin, especially if they derive from extraembryonic tissue or adult sources [240]. Importantly, as reported in the paper of Merini et al, [240] is strongly recommend that all biological issues related to the use of MSCs, such as the impact of tissue hypoxia, inflammation, and infection, should be well monitored to accelerate the transition from the bench to clinic [240]. Highlighting these features may improve the quality, safety, and efficiency of the future therapy.…”
Section: Hypoxia Aging and Stem Cell Transplantationsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations support the current view that MSCs properties are impacted by the tissue origin, especially if they derive from extraembryonic tissue or adult sources [240]. Importantly, as reported in the paper of Merini et al, [240] is strongly recommend that all biological issues related to the use of MSCs, such as the impact of tissue hypoxia, inflammation, and infection, should be well monitored to accelerate the transition from the bench to clinic [240]. Highlighting these features may improve the quality, safety, and efficiency of the future therapy.…”
Section: Hypoxia Aging and Stem Cell Transplantationsupporting
confidence: 89%
“…Slight differences exist in MSCs derived from Wharton jelly and those from the bone marrow regarding their phenotype, the telomerase activity, and the clonogenicity abilities after hypoxia or normoxia culture conditions, respectively [239]. These observations support the current view that MSCs properties are impacted by the tissue origin, especially if they derive from extraembryonic tissue or adult sources [240]. Importantly, as reported in the paper of Merini et al, [240] is strongly recommend that all biological issues related to the use of MSCs, such as the impact of tissue hypoxia, inflammation, and infection, should be well monitored to accelerate the transition from the bench to clinic [240].…”
Section: Hypoxia Aging and Stem Cell Transplantationmentioning
confidence: 56%
“…Mesenchymal stem cells (MSCs) are an important member of the stem cell family, which have been used to treat scar formation-related diseases such as pulmonary fibrosis. Moreover, great progress has been made where they have also been used to inhibit cardiac scar formation through the secretion of various cytokines [ 20 ]. Studies have shown that stem cells have been used in animal models and in a few clinical trials for the regeneration of diseased organs.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las obtenidas de médula ósea, BMMSCs, son las más probadas tanto en ensayos in-vitro como in-vivo, y la característica que más se ha evaluado en modelos experimentales y ensayos clínicos es su capacidad inmunoreguladora. 5,8,10,11 En 2006, la Sociedad Internacional de terapia celular (ISCT, por las siglas del inglés, the International Society for Cellular Therapy) determinó como tres, los criterios mínimos para caracterizar o definir las MSCs humanas (independiente de su origen), a saber: i) adherencia a superficies de plástico en condiciones de cultivo estándar; ii) presencia de marcadores de superficie mayor o igual al 95% (CD105, CD73 y CD90) y ausencia o expresión menor o igual al 2% (CD45, CD34, CD11b o CD14, CD79α o CD19 y HLA-DR); y iii) capacidad de diferenciarse a osteblastos, condroblastos y adipocitos en medios de diferenciación específicos. 12,13 Se ha descrito que las BMMSCs poseen cuatro mecanismos que posibilitan su capacidad inmunorreguladora, los cuales son:…”
Section: Mecanismos Inmunoreguladores De Las Bmmscsunclassified
“…4,5 El descubrimiento de los mecanismos moleculares asociados a esta característica, ha permitido extender su posible uso a enfermedades infecciosas y recientemente, además de las propiedades inmunorreguladoras, se han descubierto mecanismos microbicidas asociados a estas células. [6][7][8][9] Esta revisión tiene como objetivo describir los principales mecanismos moleculares e inmunológicos asociados a la capacidad inmunomoduladora de las BMMSCs y finalmente, mostrar cómo se han utilizado en algunos modelos animales de enfermedades infecciosas como la pacoccidioidomicosis, la candidiasis, la aspergilosis y la tuberculosis, entre otras.…”
Section: Introductionunclassified